Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Produk Wardah di Jakarta Barat - Latifatu Zahrah; Mohammad Amas Lahat; Dani Chandra Utama (Antartika Media Indonesia, 2026)
Tren kecantikan dan perawatan kulit telah berkembang pesat seiring dengan meningkatnya kesadaran masyarakat terhadap pentingnya menjaga kesehatan kulit dan kecantikan wajah. Setelah berkembangnya tren industri kecantikan dan perawatan, persaingan antar perusahaan perawatan dan kecantikan juga semakin ketat. Harga dan kualitas produk menjadi faktor penting yang mempengaruhi keputusan konsumen dalam melakukan pembelian. Tujuan dari penelitian ini ialah untuk mengetahui Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Pada Produk Wardah di Jakarta Barat. Metode yang dilakukan dalam penelitian ini adalah metode kuantitatif. Hasil penelitian ini membuktikan bahwa harga secara parsial memiliki pengaruh positif dan signifikan terhadap keputusan pembelian, kualitas produk secara parsial memiliki pengaruh positif dan signifikan terhadap keputusan pembelian, secara simultan harga dan kualitas produk berpengaruh positif dan signifikan terhadap keputusan pembelian. Beauty and skincare trends have grown rapidly along with increasing public awareness of the importance of maintaining healthy skin and facial beauty. Following the development of beauty and skincare industry trends, competition between skincare and beauty companies has also become increasingly fierce. Price and product quality are important factors influencing consumers' purchasing decisions. The purpose of this study is to determine the influence of price and product quality on purchasing decisions for Wardah products in West Jakarta. This study employs a quantitative research method using a survey approach, where data was collected from 100 respondents who are consumers of Wardah products in West Jakarta through a questionnaire. The study utilised SPSS Version 26 software for data analysis. The results of this study prove that price partially has (α = 0.003 and t-count = 3.013) has a positive and significant effect on purchasing decisions, while product quality partially has (α = 0.000 and t-count = 4.329) a positive and significant effect on purchasing decisions. Simultaneously, price and product quality (α = 0.000 and f-count = 79.755) have a positive and significant effect on purchasing decisions. This implies that the most effective marketing strategy should focus on an optimal balance between competitive pricing and the provision of excellent product quality, as these two elements work together to influence consumer purchasing interest.